Harmonizing Reason and Revelation in Islamic Thought: Historical Discourse on the Debate among Muslim Philosophers - Saira Jabeen Malik; Syed Muhammad Rehan Ul Hassan Gelani; Razia Shabana; Dr. Chaman Hussain (Al-Qanṭara, 2024)
This academic study begins a thorough investigation of the historical debate about the unity of revelation and reason in the Islamic tradition. Muslim thinkers, from the classical to the medieval periods, have long debated the complex relationship between reason and divine guidance. This comprehensive summary draws from a wide range of theological and philosophical frameworks to attempt to shed light on the complex character of this continuing discussion. The first part of the research explores the basic writings of early Muslim philosophers, including Al-Kindi and Al-Farabi, who established the framework for later talks about the coexistence of revelation and reason. It examines their efforts to balance the philosophical traditions of Greece and Islam, demonstrating the blending of many schools of thought that defined this early era. The abstract travels across the Islamic world of the Middle Ages, exploring the contributions of great thinkers such as Ibn Sina (Avicenna) and Ibn Rushd (Averroes). These intellectuals addressed the problems that exist between revelation and reason, offering a variety of approaches to resolving seeming contradictions. The abstract clarifies the complex metaphysical frameworks these philosophers developed, examining how they attempted to reconcile the indisputable authority of divine revelation with the pursuit of knowledge via reason. The abstract also discusses mysticism's place in this discussion, recognizing the Sufi tradition's distinct viewpoint on the integration of revelation and reason. It looks at how Sufi philosophers like Ibn Arabi added experiential elements and spiritual insights to the continuing conversation, providing a different method of bridging the gap between the revealed and the rational. This research attempts to disentangle the complex and dynamic character of the debate on harmonizing reason and revelation within the Islamic tradition by examining important philosophical texts and theological treatises. The abstract ends by emphasizing the discourse's ongoing relevance, since modern Muslim thought is still referencing these philosophical pillars in its pursuit of a harmonious fusion of revelation and reason in the contemporary world.